Conservative management of complete fetal expulsion into the abdominal cavity after silent uterine rupture - case report - Lukas Hruban; Anna Jouzova; Petr Janku; Vit Weinberger; Dagmar Seidlova; Tomas Juren; Jan Senkyrik; Jana Kadlecova; Jitka Hausnerova; Eva Jandakova (BMC, 2023)
Abstract Background Clinically silent uterine rupture with complete fetal expulsion into the abdominal cavity is an extremely rare complication. Diagnosis can be difficult and the risk to the mother and fetus is high. Conservative management has been described only in a few cases of partial expulsion of the fetus so far. Case presentation We present a case of 43-year-old tercigravida with a history of previous laparotomic myomectomy and subsequent cesarean section. The subsequent pregnancy was complicated by uterine wall loosening and rupture at the site of the previous uterine scar after myomectomy and complete fetal expulsion into the abdominal cavity. The diagnosis was made at 24 + 6 weeks of gestation. Considering the absence of clinical symptomatology and the good condition of the fetus, a conservative approach was chosen with intensive monitoring of the maternal and fetal conditions. The pregnancy ended by elective cesarean section and hysterectomy at 28 + 0 weeks of gestation. The postpartum course was uneventful and the newborn was discharged to home care 63 days after delivery. Conclusions Fetal expulsion into the abdominal cavity after silent uterine rupture of the scarred uterus may be accompanied by minimal symptomatology making early diagnosis difficult. This rare complication must be considered in the differential diagnosis in women after major uterine surgery. In selected cases and under conditions of intensive maternal and fetal monitoring, conservative management may be chosen to reduce the risks associated with prematurity.